2009 Data Compression Conference 2009
DOI: 10.1109/dcc.2009.53
|View full text |Cite
|
Sign up to set email alerts
|

H.264/MPEG-4 AVC Encoder Parameter Selection Algorithms for Complexity Distortion Tradeoff

Abstract: The H.264 encoder has input parameters that determine the bit rate and distortion of the compressed video and the encoding complexity. A set of encoder parameters is referred to as a parameter setting. We previously proposed two offline algorithms for choosing H.264 encoder parameter settings that have distortion-complexity performance close to the parameter settings obtained from an exhaustive search, but take significantly fewer encodings. However they generate only a few parameter settings. If there is no a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The number of executions of this process (N Run_ Before ) is proportional to the total number of non-zero coefficients (TotalCoeffs) and total number of zeros before the highest nonzero coefficient (Totzeros). Considering the number of search operations for each combination of (TotalCoeffs, Totzeros) and using the curve fitting tool of MATLAB, we have extracted the macroblock level complexity parameter of this process as shown in formula (12).…”
Section: Trailing Ones Decodingmentioning
confidence: 99%
“…The number of executions of this process (N Run_ Before ) is proportional to the total number of non-zero coefficients (TotalCoeffs) and total number of zeros before the highest nonzero coefficient (Totzeros). Considering the number of search operations for each combination of (TotalCoeffs, Totzeros) and using the curve fitting tool of MATLAB, we have extracted the macroblock level complexity parameter of this process as shown in formula (12).…”
Section: Trailing Ones Decodingmentioning
confidence: 99%
“…The authors propose two fast approaches that do not require an exhaustive evaluation of encoder configurations. An extension of this work is presented in [19] following the same principles. In [20], an allocation of computational resources based on a virtual buffer is proposed.…”
Section: B Complexity Control In H264/avcmentioning
confidence: 99%
“…An improvement to the work presented in [8] was proposed by the same authors in [4], in which two further algorithms for finding additional parameter settings for the GBFOS-basic algorithm were presented. However, a significant constraint of the work of [7,3] is its limited use only within two constraints namely, complexity and video quality.…”
Section: H264 Video Codecmentioning
confidence: 99%
“…In [3] it was shown that the approach presented in [4] cannot be easily extended to other video encoders. It presented a novel power-rate-distortion (P-R-D) optimization algorithm that can be used to minimize energy consumption of delay tolerant applications in portable video communication.…”
Section: Related Workmentioning
confidence: 99%